Advances in the study of nicotinamide adenine dinucleotide phosphate oxidase in myocardial remodeling - Miao, Runran; Wang, Libo; Chen, Zhigang; Ge, Shiqi; Li, Li; Zhang, Kai; Chen, Yingen; Guo, Wenjing; Duan, Xulei; Zhu, Mingyang; Zhao, Guoan; Lin, Fei (Frontiers in Cardiovascular Medicine, 2022)
Myocardial remodeling is a key pathophysiological basis of heart failure, which seriously threatens human health and causes a severe economic burden worldwide. During chronic stress, the heart undergoes myocardial remodeling, mainly manifested by cardiomyocyte hypertrophy, apoptosis, interstitial fibrosis, chamber enlargement, and cardiac dysfunction. The NADPH oxidase family (NOXs) are multisubunit transmembrane enzyme complexes involved in the generation of redox signals. Studies have shown that NOXs are highly expressed in the heart and are involved in the pathological development process of myocardial remodeling, which influences the development of heart failure. This review summarizes the progress of research on the pathophysiological processes related to the regulation of myocardial remodeling by NOXs, suggesting that NOXs-dependent regulatory mechanisms of myocardial remodeling are promising new therapeutic targets for the treatment of heart failure.